Modified cognitive behavioral therapy approach reduces loudness discomfort levels for an autistic child with hyperacusis: case report - Carson, Tana B.; Guerrero, Lisa A.; Niebles, Monica; Gayle, Cindi G. F. (Frontiers in Psychiatry, 2024)
Introduction Hyperacusis is common among the autistic population, with a lifetime prevalence estimated at up to 60% compared to 17.1% in those without autism. For autistic children, avoidance behaviors and distress associated with hyperacusis significantly disrupt participation in everyday routines including academic, social and leisure activities. Although hyperacusis is a significant problem for children with autism and their families, there is little research on effective interventions. This report describes the clinical case of an 11-year-old boy with autism who received a modified cognitive behavioral therapy (CBT) approach to address symptoms of hyperacusis. Case presentation Patient A is an 11-year-old boy with autism and hyperacusis. He and his parents report difficulties tolerating loud or high-pitched sounds including whistling, fireworks, traffic and high-pitched musical instruments (e.g., the ocarina and flute). When hearing these sounds during everyday activities (e.g., celebrations and social events) he will often ask strangers to stop, cover his ears, or avoid/run away from the source of sound. A modified CBT approach was combined with exposure therapy, and sensory-based self-regulation strategies to improve tolerance and decrease distress when hearing whistling. Treatment outcomes include improved loudness discomfort levels in audiology evaluations, improved auditory domain scores on the Sensory Profile questionnaires, lower self-reported subjective units of distress scale (SUDS) ratings in response to bothersome sounds, and decreased use of noise canceling headphones during daily activities. The client and his parents also reported generalization of these improvements with other sounds (e.g., fireworks). Conclusion The patient described in this case report showed measurable improvements in his ability to tolerate whistling, a bothersome sound encountered regularly in his daily life. Considering the high prevalence rate of hyperacusis in autism and its impact on children and family routines, stress and daily living, the development and testing of an effective treatment approach for hyperacusis is needed. The treatment plan for this case arose from the collaboration between professionals in occupational therapy, applied behavior analysis, audiology, and clinical psychology. Future studies are encouraged to determine the efficacy of this combined approach for other children with autism and hyperacusis.